Heteroconium tulsiense (Antennulariellaceae): a novel microfungus from Sanjay Gandhi National Park, Maharashtra, India - Dubey, Rashmi; Pandey, Amit D. (Phytotaxa, 2022)
Heteroconium tulsiense is a new species collected on dry twig litter at Tiger Reserve areas (Tulsi Range), Sanjay Gandhi National Park, Mumbai, Maharashtra, India. It is illustrated, described and compared with related taxa. This fungus is characterized by unevenly pigmented conidia having pale brown ends, and produced in chains of up to four. The isolate was identified on the basis of its asexual morph. A key to 20 valid species of Heteroconium is presented.